2017
DOI: 10.1016/j.jns.2017.07.044
|View full text |Cite
|
Sign up to set email alerts
|

Linking Alzheimer's disease and type 2 diabetes: Novel shared susceptibility genes detected by cFDR approach

Abstract: Our study provided evidence for shared genetic loci between T2D and AD in European subjects by using cFDR and ccFDR analyses. These results may provide novel insight into the etiology and potential therapeutic targets of T2D and/or AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 85 publications
(104 reference statements)
0
29
0
Order By: Relevance
“…They found an enrichment for SNPs associated with cognitive impairment conditional on plasma CRP and lipids, and significant associations for the APOE extended locus 36 . Shared genetic etiology for LOAD using the cFDR method was also investigated for Type 2 diabetes (T2D) 37 . In this study, multiple known and novel associated SNPs were identified by conditioning LOAD association on T2D and by the reverse direction, and mitochondrial dysfunction was highlighted as a common pathway 37 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…They found an enrichment for SNPs associated with cognitive impairment conditional on plasma CRP and lipids, and significant associations for the APOE extended locus 36 . Shared genetic etiology for LOAD using the cFDR method was also investigated for Type 2 diabetes (T2D) 37 . In this study, multiple known and novel associated SNPs were identified by conditioning LOAD association on T2D and by the reverse direction, and mitochondrial dysfunction was highlighted as a common pathway 37 .…”
Section: Discussionmentioning
confidence: 99%
“…The pleiotropy analysis strategy, based on conditional false discovery rates, fold-enrichment plots, and conditional quantile-quantile (Q-Q) plots, is described in detail elsewhere 28,37 . In brief, for two phenotypes A and B, pleiotropic enrichment of phenotype A conditional on phenotype B exists if the proportion of variants (SNPs) statistically significantly associated with phenotype A increases as a function of increased statistically significant SNP associations with phenotype B.…”
Section: Statistical and Bioinformatics Analysis Pleiotropy Analysismentioning
confidence: 99%
See 3 more Smart Citations